Ideas of individuals and gradation of yucή hypostasis in Enneads by Plotinus - Woszczyk, Agnieszka (Folia Philosophica, 2010)
The paper deals with the problems of the ideas of individuals in Plotinus’ system. The author claims that the concept as described in Enneads should not be seen as separate from the principles of Plotinus’ ontology. It may be proofed by pointing out the psychological context in which Plotinus puts this issue and the kind of understanding of noetic sphere in terms of multitude, which entails the individualization of souls, typical for Plotinus. He takes the ideas of individuals as connected with the concept of alethēs anthropos - the essential way of being of a man in the hypostasis of the Intellect (nous).